Occurrence and outcome after primary treatment of anal fistulae in Crohn's disease. Issue 6 (June 1980) - Hellers, G; Bergstrand, O; Ewerth, S; Holmström, B
Abstract : During the period 1955 to 1974 inclusive, 826 patients developed Crohn's disease and were registered citizens of Stockholm County at the time of definite diagnosis. These patients were followed up and investigated with reference to the occurrence of and outcome after treatment for anal fistulae. These fistulae were recorded in 184 patients (23%). The incidence of anal fistulae increased the further distally the intestinal lesion was located. Healing followed local operation for anal fistula before curative intestinal resection in approximately 60% of the patients with small intestinal and combined ileocolic disease. However, patients with colonic Crohn's disease did not heal after such treatment. When curative intestinal resection was the primary procedure, 47% of the patients healed spontaneously. Small intestinal and combined ileocolic disease was associated with a good prognosis–90% were healed at follow-up, while patients with colonic disease had a poor prognosis. The combination of rectal Crohn's disease and anal fistula invariably led to proctocolectomy.